Literature Review The Effect Of Blood Supplements Tablet On Adolescent Girls In Anemia - Alya Nafis; Indah Laily Hilmi (Sean Institute, 2022)
According to data from Riset Kesehatan Dasar (Riskesdas) in 2018, the prevalence of anemia in Indonesia was 48.9%, with the highest prevalence of anemia at the age of 15-24 years and the least at the age of 45-54 years. Factors for the occurrence of iron nutritional anemia in adolescent girls include lack of education about iron nutritional anemia, unsupportive environmental factors, lack of attention to daily nutritional intake, and lack of implementation of preventive measures from the government by consuming blood-added tablets. This study uses the review article method with research data sources based on journal publications on the internet. Based on the results of the review article conducted, it can be concluded that the effect of giving blood-added tablets can increase hemoglobin (Hb) levels so as to avoid the incidence of anemia (Hb <12 mg/dL) and reduce the prevalence of anemia in Indonesia..